The complete chloroplast genome of a Woodwardia japonica - Ramekar, Rahul Vasudeo (Mitochondrial DNA B Resour, 2019)
Woodwardia japonica is one of the diverse members of the fern group and medicinally important genus. In Korea, the natural resources of W. japonica are being exhausted by excessive exploitation and require urgent conservation. In this study, the complete chloroplast genome of W. japonica was generated, and its structure was compared with that of other members of same family. The chloroplast genome was 153224 bp long, with a typical quadripartite structure including a pair of inverted repeat regions (24591 bp) separated by a large (82480 bp) and small (21562 bp) single-copy (SC) region. The genome encodes a total of 88 protein-coding genes, 35 tRNA genes, and eight rRNA genes. Additionally we identified 87 RNA editing sites in 52 genes; most of the substitution was U to C (50 sites), while C to U conversion occurred in 37 positions. The phylogenetic analysis strongly supported the relationship of W. japonica with W. unigemmata and. A. melanocaulon (Blechnoideae).